SPECTROFLUORIMETRIC DETERMINATION OF LEVOFLOXACIN IN PHARMACEUTICALS AND IN HUMAN URINE : Life Science-Pharmaceuticls analysis - PEIXOTO DA SILVA, ARNALDO; SEVERINO LUNA, ADERVAL; MALCHER DA SILVA COSTA, THAIS; QUEIROZ AUCELIO, RICARDO; WILLIAN BATISTA BRAGA, JEZ; BOQUÉ, RICARD; FERRÉ, JOAN (International Journal of Life Science and Pharma Research, 2012)
Two spectrofluorimetric methods are proposed to determine levofloxacin in pharmaceutical tablets and spiked human urine. The first method allowed the determination of levofloxacin in aqueous solution using univariate (zero order) calibration. The analytical curve was linear to a concentration of levofloxacin of, at least, 300 ng mL-1 and the coefficient of correlation was 0.9988. The accuracy was evaluated using three different concentrations and the mean recovery was 97.6 ± 6.5% and the mean precision was lower than 2.0%, except for the concentration of 180 ng mL-1 for the analyst 2. The limit of detection (LOD) was 0.46 ng mL-1, which can be considered adequate for this purpose. The method showed a good concordance when it was applied to Brazilian pharmaceutical formulation with a relative standard deviation of 3.5%. The second method used parallel factor analysis with standard additions for the determination of levofloxacin in urine. The scores, related to levofloxacin, were used to quantify levofloxacin in human urine, using linear regression and the standard additions method. The LOD was 1.4 ng mL-1 for urine sample diluted 1000 times with a mean precision of 3.0 ng. mL-1 and a root mean square error of calibration of 8.0 ng mL-1. An additional application of this method was carried out to monitoring the levofloxacin in urine sample from a healthy man until of a complete excretion of this antibiotic with success.